2015
DOI: 10.1002/pros.23136
|View full text |Cite
|
Sign up to set email alerts
|

The STEAP1262–270 peptide encapsulated into PLGA microspheres elicits strong cytotoxic T cell immunity in HLA‐A*0201 transgenic mice—A new approach to immunotherapy against prostate carcinoma

Abstract: BACKGROUND. PLGA microsphere-based vaccination has been proven to be effective in immunotherapy of syngeneic model tumors in mice. The critical step for the translation to humans is the identification of immunogenic tumor antigens and potent vaccine formulations to overcome immune tolerance. METHODS. HLA-AÃ 0201 transgenic mice were immunized with eight different human prostate cancer peptide antigens co-encapsulated with TLR ligands into PLGA microspheres and analyzed for antigen-specific and functional cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…weak self-antigens in tumor tissue. While soluble peptide immunizations elicited only very poor CD8+ T cell responses, microencapsulation of the HLA-A * 0201 restricted immunodominant epitope STEAP 1 (six transmembrane epithelial antigen of the prostate) was shown to induce potent prostate cancer peptide-specific CTL activation and cytotoxic effector function (36, 41).…”
Section: Properties Of Plga Particlesmentioning
confidence: 99%
“…weak self-antigens in tumor tissue. While soluble peptide immunizations elicited only very poor CD8+ T cell responses, microencapsulation of the HLA-A * 0201 restricted immunodominant epitope STEAP 1 (six transmembrane epithelial antigen of the prostate) was shown to induce potent prostate cancer peptide-specific CTL activation and cytotoxic effector function (36, 41).…”
Section: Properties Of Plga Particlesmentioning
confidence: 99%
“…ELISPOT assay ELISPOT was performed as detailed previously. 38 The spots were assessed with an ImmunoScan reader (CTL, Bonn, Germany).…”
Section: Western Blottingmentioning
confidence: 99%
“…More recently, clinical studies employing humanized variants of mAb120.545 that target STEAP1 were conducted, including: 1) a phase I trial using an antibody-drug-conjugate (termed DSTP3086S or Vandortuzumab Vedotin) to target prostate cancer (6)(7)(8), and 2) a combined Phase I / Phase II trial for the PET-imaging of metastatic castration-resistant prostate cancer patients using Zr 89 labelled antibody (termed [ 89 Zr]Zr-DFO-MSTP2109A) (9)(10)(11). Besides antibody-based strategies, several in vitro and in vivo studies revealed that STEAP1-derived peptides are immunogenic and thus suitable for recognition by cytotoxic T lymphocytes (12)(13)(14)(15)(16), indicating that STEAP1 could represent a potential candidate for the development of anticancer vaccines (4,17). STEAP1 belongs to a protein family that comprises three metalloreductases (18,19) (STEAP2-4, also known as STAMP1-3 (20)(21)(22) ), which reduce iron(III) and copper(II) and are also associated with cancer progression (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%